A RNA-seq approach for exploring the protective effect of ginkgolide B on glutamate-induced astrocytes injury. (24th April 2021) - Wang, Jing; Zhuang, Linwu; Ding, Yan; Wang, Zhenzhong; Xiao, Wei; Zhu, Jingbo
Abstract: Ethnopharmacological relevance: There is substantial experimental evidence to support the view that Ginkgo biloba L. (Ginkgoaceae), a traditional Chinese medicine known to treating stroke, has a protective effect on the central nervous system and significantly improves the cognitive dysfunction caused by disease, including alzheimer disease (AD), vascular dementia, and diabetic encephalopathy. Although a number of studies have reported that ginkgolide B (GB), a diterpenoid lactone compound extracted from Ginkgo biloba leaves, has neuroprotective effects, very little research has been performed to explore its potential pharmacological mechanism on astrocytes under abnormal glutamate (Glu) metabolism in the pathological environment of AD. Aim of the study: We investigated the protective effect and mechanism of GB on Glu-induced astrocytes injury. Methods: Astrocytes were randomly divided into the control group, Glu group, GB group, and GB + IWP-4 group.The CCK-8 assay was used to determine relative cell viability in vitro . Furthermore, RNA sequencing (RNA-seq) was performed to assess the preventive effects of GB in the Glu-induced astrocyte model and reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to validate the possible molecular mechanisms. The effects of GB on the Glu transporter and Glu-induced apoptosis of astrocytes were studied by RT-qPCR and western blot. Results: GB attenuated Glu-induced apoptosis in a concentration-dependent manner, while the Wnt inhibitor IWP-4 reversed the protective effect of GB on astrocytes. The RNA-seq results revealed 4, 032 differential gene expression profiles; 3, 491 genes were up-regulated, and 543 genes were down-regulated in the GB group compared with the Glu group. Differentially expressed genes involved in a variety of signaling pathways, including the Hippo and Wnt pathways have been associated with the development and progression of AD. RT-qPCR was used to validate 14 key genes, and the results were consistent with the RNA-seq data. IWP-4 inhibited the regulation of GB, disturbed the apoptosis protective effect on astrocytes, and promoted Glu transporter gene and protein expression caused by Glu. Conclusion: Our findings demonstrate that GB may play a protective role in Glu-induced astrocyte injury by regulating the Hippo and Wnt pathways. GB was closely associated with the Wnt pathway by promoting expression of the Glu transporter and inhibiting Glu-induced injury in astrocytes. Graphical abstract: Image 1